1969
DOI: 10.1126/science.163.3874.1452
|View full text |Cite
|
Sign up to set email alerts
|

Serine Requirement in Leukemic and Normal Blood Cells

Abstract: In a serine-deficient medium, cells from humangt chronic granulocytic leukemia and normal human bone marrow exhibited a marked inhibition of incorporation of-radioactive precursors of DNA, RNA, and protein into an acid insoluble cell fraction. Normal diploid human fibroblasts did not exhibit inhibition without serine. Chronic granulocytic leukemia and normal marrow cells were essentially unable to synthesize C(14)-serine from C(14)-glucose, while human diploid fibroblasts were highly capable of this synthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

1971
1971
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 6 publications
1
10
0
Order By: Relevance
“…For CML, similar to our analysis, several studies have shown that levels of glutamate, serine, which is a precursor of cysteine, and alanine are increased by CML (153)(154)(155). Consistent with these NEAAs playing an important role in CML, restriction of serine (156,157) and its derivatives glycine (156), or cysteine (158,159) decreases CML proliferation, supporting that targeting these NEAA pathways may be a potential target for CML.…”
Section: Restriction Of Other Neaas Derived From Glutamate Decrease Myeloid Leukemia Proliferationsupporting
confidence: 88%
“…For CML, similar to our analysis, several studies have shown that levels of glutamate, serine, which is a precursor of cysteine, and alanine are increased by CML (153)(154)(155). Consistent with these NEAAs playing an important role in CML, restriction of serine (156,157) and its derivatives glycine (156), or cysteine (158,159) decreases CML proliferation, supporting that targeting these NEAA pathways may be a potential target for CML.…”
Section: Restriction Of Other Neaas Derived From Glutamate Decrease Myeloid Leukemia Proliferationsupporting
confidence: 88%
“…Serine levels were increased significantly ( p adj 9.9 × 10 −5 ) in the pellets of leukemia cells, whereas the opposite ( p adj 2.5 × 10 −9 ) was observed in the corresponding supernatants. Since serine is an essential amino acid for leukemic cells , this might explain our findings of increased serine uptake and subsequent conversion to glycine.…”
Section: Resultsmentioning
confidence: 79%
“…Of the amino acids regarded as nutrition ally nonessential, L-serine has been report ed to be required for optimal growth of rab bit fibroblasts [Hajj and Swim, 1956], hu man chronic granulocytic leukemia cells and normal human bone marrow cells [Regan et al, 1969]. Monkey kidney cells require gly cine [Eagle et al, 1958] and both glycine and L-serine are required for optimal growth of Novikoff hepatoma cells [McCoy et al, 1959] and Walker carcinosarcoma 256 cells [McCoy et al, 1956].…”
Section: Discussionmentioning
confidence: 99%